'The whole world's watching really': Parental and educator perspectives on managing children's digital lives. Issue 2 (June 2019) - Buchanan, Rachel; Southgate, Erica; Smith, Shamus P
Teachers are under increased pressure to teach children digital skills, and parents are having to manage children's online presence as well as their offline lives. Much of the discussion surrounding the issue of children's digital footprints highlights the potential present and future risks that children could be exposed to. While parents and teachers are expected to educate and protect children online, little is known about what parents and educators know in the Australian context and how they feel about being the custodians of children's digital presence. The purpose of this article is twofold. Firstly, the authors report on the Best Footprint Forward project, which employed focus groups to qualitatively investigate the digital-footprint awareness of parents and teachers from three primary schools in regional Australia. Secondly, the authors outline an ethical framework that can be used to provide guidance to those who teach children on how to manage their online presence. Parents and teachers were very aware of the issues surrounding digital-footprint management and cyber safety for children, but had little awareness of the positive potential of digital footprints or how to help children manage their digital lives. In reporting the uncertainty experienced by these two groups, the authors seek to highlight the ethical complexities of children's participation in digital cultures and provide a framework for engaging with these complexities.